Smoking Intention and Social Support toward Smoking Behavior among Male Adolescents - Murti, Christinauli Eka; Ayu, Ira Marti; Shorayasari, Susi; Veronika, Erna; Nitami, Mayumi; Heryana, Ade (Jurnal Kesmas Jambi, 2025)
The prevalence of smoking among children and adolescents in Indonesia has been reported to have significantly increased, with more male adolescents smoking than female adolescents. A preliminary study conducted at SMAN X, Tangerang Regency, found that 7 out of 20 male students (35%) reported smoking. The high prevalence of smoking among adolescent males could lead to more serious health issues in the future. This study aims to identify the factors associated with smoking behaviour among male adolescents at SMAN X Tangerang Regency in 2024. The study used a cross-sectional study with 72 sample sizes of male adolescents. The sampling technique used in this study was total sampling. The researcher collected data from April to August 2024. Primary data was collected through a questionnaire. Data were analyzed using univariate and bivariate analysis with chi-square tests. Univariate results show the highest proportions: non-smoking behaviour (69.4%), low intention to smoke (83.3%), unsupportive social environment (56.9%), and exposure to health information (61.1%). Bivariate results reveal a relationship between intention to smoke (PR=2.86, 95%CI=1.56 to 5.25) and social support (PR=4.50, 95%CI=1.86 to 10.86) with smoking behaviour. The school should continue its efforts to prohibit smoking among students by posting posters about the dangers of smoking and signs prohibiting smoking, as well as implementing a program involving the role of guardians/parents to actively monitor and educate adolescent males about the dangers of smoking so that they do not smoke.